Parallelogram inside a parallelogram

Geometry Level 4

The A B C D ABCD is a paralleolgram. The midpoints of the A B , B C , C D , A D AB, BC, CD, AD sides are E , F , G E, F, G and H H , respectively. The perimeter of the A B C D ABCD parallelogram is K K , and the perimeter of the E F G H EFGH quadrilateral is k k . We know that D A B = 60 ° \angle DAB=60° .

If the minimum value of k K \dfrac{k}{K} is a + b c \dfrac{a+\sqrt{b}}{c} , where a , b a, b and c c are integers, and b b is square-free, then find the value of a + b + c a+b+c .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Oct 16, 2017

Relevant wiki: Arithmetic Mean - Geometric Mean

Let A D = B C = a AD=BC = a and A B = C D = b AB=CD=b , then K = 2 ( a + b ) K=2(a+b) . By cosine rule:

E H 2 = A H 2 + A E 2 2 A H A E cos D A B = a 2 4 + b 2 4 2 a 2 b 2 cos 6 0 E H = a 2 + b 2 a b 2 \begin{aligned} \overline{EH}^2 & = \overline{AH}^2 + \overline{AE}^2 - 2 \cdot \overline{AH} \cdot \overline{AE} \cos \angle DAB \\ & = \frac {a^2}4 + \frac {b^2}4 - 2 \cdot \frac a2 \cdot \frac b2 \cos 60^\circ \\ \implies \overline{EH} & = \frac {\sqrt{a^2+b^2-ab}}2 \end{aligned}

Similarly,

H G 2 = a 2 4 + b 2 4 2 a 2 b 2 cos 12 0 H G = a 2 + b 2 + a b 2 \begin{aligned} \overline{HG}^2 & = \frac {a^2}4 + \frac {b^2}4 - 2 \cdot \frac a2 \cdot \frac b2 \cos 120^\circ \\ \implies \overline{HG} & = \frac {\sqrt{a^2+b^2+ab}}2 \end{aligned}

Therefore, k = a 2 + b 2 a b + a 2 + b 2 + a b k = \sqrt{a^2+b^2-ab} + \sqrt{a^2+b^2+ab} and

k K = a 2 + b 2 a b + a 2 + b 2 + a b 2 ( a + b ) = 1 2 ( a 2 + 2 a b + b 2 3 a b a 2 + 2 a b + b 2 + a 2 + 2 a b + b 2 a b a 2 + 2 a b + b 2 ) = 1 2 ( 1 3 a b a 2 + 2 a b + b 2 + 1 a b a 2 + 2 a b + b 2 ) = 1 2 ( 1 3 a b + 2 + b a + 1 1 a b + 2 + b a ) By AM-GM inequality a b + b a 2 1 2 ( 1 3 4 + 1 1 4 ) = 1 + 3 4 \begin{aligned} \frac kK & = \frac {\sqrt{a^2+b^2-ab} + \sqrt{a^2+b^2+ab}}{2(a+b)} \\ & = \frac 12 \left(\sqrt{\frac {a^2+2ab+b^2-3ab}{a^2+2ab+b^2}} + \sqrt{\frac {a^2+2ab+b^2-ab}{a^2+2ab+b^2}} \right) \\ & = \frac 12 \left(\sqrt{1-\frac {3ab}{a^2+2ab+b^2}} + \sqrt{1-\frac {ab}{a^2+2ab+b^2}} \right) \\ & = \frac 12 \left(\sqrt{1-\frac 3{{\color{#3D99F6}\frac ab}+2+\color{#3D99F6}\frac ba}} + \sqrt{1-\frac 1{{\color{#3D99F6}\frac ab}+2+\color{#3D99F6}\frac ba}} \right) & \small \color{#3D99F6} \text{By AM-GM inequality } \frac ab + \frac ba \ge 2 \\ & {\color{#3D99F6} \le} \ \frac 12 \left(\sqrt{1-\frac 3{\color{#3D99F6}4}} + \sqrt{1-\frac 1{\color{#3D99F6}4}} \right) \\ & = \frac {1+\sqrt 3}4 \end{aligned}

a + b + c = 1 + 3 + 4 = 8 \implies a+b+c = 1+3+4 = \boxed{8}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...